Archaeometry Research of Lithic Raw Materials for Early Prehistoric Communities with PGAA - Kasztovsky, Zsold; Biro, Katalin; Marko, Andras; Burić, Marcel; Šošić Klindžić, Rajna; Težak-Gregl, Tihomila (2009)
Obsidian is a favourite subject of archaeometrical studies. Radiolarite is of comparable significance, however, much less analyzed yet. In the earliest phase of the Neolithic, both obsidian and radiolarite are important markers of the movements of goods and people trading them. There is no local obsidian on the territory of Croatia: import, however, may originate from both the Carpathian Basin and the Mediterranean region. The importance of radiolarites is adequately demonstrated in Hungary by now. It is apparent, however, that there is essential local supply of various radiolarites in Croatia, too. In addition, there is considerable (supposed) import from the territory of Hungary. Thus, we wish to find objective discrimination features to define these supply zones and the border of these zones. The research is done in a 2008-2009 Croatian-Hungarian and funded by Hungarian Science and Technology Foundation (TéT), with the aims of sampling and identification of potential obsidian and radiolarite sources in Croatia and in Hungary. The basic analytical method is Prompt Gamma Activation Analysis.
Projekt MZOS
ENG